ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI DALAM MELAKUKAN ALIH USAHATANI PADI KE USAHATANI BUAH NAGA (STUDI KASUS DI DESA SUMBERAGUNG KECAMATAN PESANGGARAN KABUPATEN BANYUWANGI) - Agus Setiawan; Jani Januar (University of Jember, 2021)
Sumberagung Village is one of the villages in Pesanggaran Subdistrict, Banyuwangi Regency, which has the potential to become a dragon fruit production center in Pesanggaran Subdistrict because it has quite a large planting area. The purpose of this study was to analyze the factors that influence the decision of farmers in transferring rice farm management to dragon fruit farm management and to analyze the differences in income between rice farm management and dragon fruit farm management. The determination of the area was carried out using a purposive method. The sampling technique used cluster sampling. The method of analysis used logistic regression and t-test. Of the research: (1) The factors that significantly influence the farmer's decision making in changing the farm management are: income and land area, with a significance value of 0.025; and 0.021. (2) There is a significant difference between the income of a rice farm management farmer and a dragon fruit farm management farmer. The average income of rice farmer was IDR 38.756.378 / Ha / year, while dragon fruit farmer had an average income of IDR 116.741.669 / Ha / year.